Gamma ray fluorescence for in situ evaluation of ore in Witwatersrand gold mines - Rolle, Rainer (My University, 2015)
A system tor quantitative in situ evaluation of ore in Witwatersrand gold mines was researched and subsequently developed. The principle of measurement is based on the excitation of gold K x-rays in rock face samples by the 88 keV gamma radiation from a Cadmium-109 radioisotope source. The X-rays and scattered radiation from the rock matrix are detected by a hyperpure germanium detector cooled by liquid nitrogen in a portable probe. In the fluorescence spectrum the intensity ratio of the gold Kb peaks to their immediate scattered background is evaluated and quantitatively converted in the portable analyser to area concentration units. All aspects of the physical and instrumental measurement had to be investigated to arrive at a system capable ot quantitative evaluation of trace concentrations in stope face ore samples. The parameters of efficiency of excitation of the gold K X-rays, and the energy distribution after scattering from the rock matrix at different angles were investigated from basic principles to determine an optimum source - sample - detector g e o m e t r y which would allow quantitative evaluation of homogeneous ore concentrations, for edged-on measurement of rough-surfaced thin layer deposits a method or controlling the measurement geometry through ratemeter feedback was developed to allow conversion of mass concentration values to units of area concentration. The parameters of spectrum evaluation were investigated from fundamental principles to allow quantitative assessment of different methods of peak evaluation for optimization of the method as a whole. The basic concepts of random signal processing times were developed together with new concepts of pileup parameters to allow a quantitative description of the data acquisition rate of a complete analog pulse processing system. With this foundation a practical measuring geometry and optimum values for signal processing time parameters, for detector size and for discriminator positions for spectrum evaluation could be determined. Parallel with the derivation of optimum measurement parameters went the development of instruments, their field testing and appraisal of the method. The underground results obtained with prototype versions of the gamma ray fluorescence analyser were in all instances found to have a highly significant correlation with those obtained from the same locations by conventional chip or bulk sampling and fire assay. The development of the gamma ray fluorescence method has shown the potential of the method to serve as an ore valuation tool and to assist in the geological identificaion of strata in Witwatersrand gold mines.
A Thesis Submitted to the Faculty of Science University of the Witwatersrand, Johannesburg for the Degree of Doctor of Philosophy Johannesburg 1979